Van anders naar alledaags : De veranderende Nederlandse houding ten opzichte van de Indische keuken - Toussaint, Suzanne (Skript Historisch Tijdschrift, 2025)
In examining the change in Dutch attitudes towards the Indisch (a complex term with reference to the colonial history of the Dutch Indies) cuisine, this paper argues that a culinary appropriation narrative has been dominant in research of this subject. However, this narrative fails to capture the full complexity of the shifting Dutch perceptions towards the Indisch cuisine. While we should consider this narrative, other factors also influenced the shift in Dutch attitudes, such as the media, increasing prosperity, technological innovations, globalisation, and multiculturalism. The findings in this article suggest that the Dutch attitudes towards the Indisch cuisine were shaped by a dynamic interplay of historical, social, and cultural factors, which challenges the dominant narrative of culinary appropriation and highlights the importance of considering broader contexts when analysing cultural change.